Human DNA Replicates Solar System - Subba Rao, Y. V. (European Journal of Applied Sciences, 2021)
The study presents that Human DNA is plausibly an exact replica of the Solar System in that the planets of the solar system are the cosmic counterparts of all DNA components that hold a relationship with the significations of planets in ‘Jyotish (Astrology). A plausible relationship is being observed between the molecular weights of individual bases of DNA Bonds and the mass of planets, between the bonding of the DNA base pairs and the empathy of planets and between the DNA Bonds and the planets genders as signified in ‘Jyotish’. The ‘genomic DNA’, the famous molecule of heredity is also observed to probably bear an identical relationship with the planetary configurations in the zodiac. More importantly, a relationship between the composition of ‘morphological DNA’ with the Sun and Moon (Earth’s Satellite) being the central planets of heliocentric and geocentric models respectively is also being observed. The frequency of morphological DNA in resonance with the frequency of solar magnetic canals plausibly result in coding of DNA in the panspermia origin of life and decoding the same in evolution on earth.